Peasant Uprisings in Astarabad: the Siyāh Pūshān (wearers of black), the Sayyids, and the Safavid State. Issue 3 (3rd May 2016) - Jurdi Abisaab, Rula
Abstract : Rebellions bringing together peasant-pastoralists, local dignitaries, and a few Sayyids prevented the Safavid monarchs from effectively controlling the political and economic activities in the province of Astarabad until the late sixteenth century. This paper investigates the nature of these rebellions led by the siyāh pūshān (wearers of black), and the socio-economic background and religious leanings of these rebels and their diverse allies. It also pays special attention to Astarabad's Sayyids, their intellectual formation, and their distinct approaches to the Safavid state from the early sixteenth century until the late 1570s when the uprisings lost much of their vigor. While heterodoxy may have been part of Astarabad's religious landscape, there is no evidence that it had a significant manifestation in the Siyah Push movement. More importantly, urban Shiʿi doctrinal and legal traditions had profound roots in Astarabad, nurtured by the Sayyids and promoted by the Betekchi dignitaries prior to the rise of the Safavids. This is significant given the fact that a group of Sayyids from Astarabad (especially the town of Fenderesk) were directly involved in the insurgency against the early Safavids.